2019
DOI: 10.1111/1758-2229.12733
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial intracellular nanoparticles exhibiting antioxidant properties and the significance of their formation in ROS detoxification

Abstract: Summary Biogenic magnetic nanoparticles (BMNPs) can be formed by numerous microorganisms. However, the significance of their formation and their possible functions have not been explored in detail. To explore a possible function of Fe3O4 NPs in Burkholderia sp. strain YN01, we investigated their catalytic abilities in the elimination of intracellular reactive oxygen species (ROS). Changes in ROS content under different conditions were assessed and showed that low oxygen and high iron concentrations in the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In a recent study with magnetotactic bacteria ( Burkholderia sp. ), Pan et al had concluded that the MNPs in the bacteria help in the efficient scavenging of excess ROS, by the antioxidase-like activity of iron crystals [35] . The MNPs observed in the pathogenic bacteria might also follow a similar strategy to overcome ROS-induced toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study with magnetotactic bacteria ( Burkholderia sp. ), Pan et al had concluded that the MNPs in the bacteria help in the efficient scavenging of excess ROS, by the antioxidase-like activity of iron crystals [35] . The MNPs observed in the pathogenic bacteria might also follow a similar strategy to overcome ROS-induced toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…activities and can effectively inhibit oxidative stress in the cellular environment. [26] Here, we selected an electro-active bacterium, S. oneidensis MR-1, as a model to demonstrate its unique biotic-abiotic interface behavior, owing to its ability to anaerobically produce hydrogen gas and biosynthesize CdS and Fe 3 O 4 nanoparticles. We investigated whether the simultaneous synthesis of highly light-collecting CdS nanoparticles and Fe 3 O 4 nanozymes on the cell surface could be used more efficiently for hydrogen production by exploiting bacterial bioreactions.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic iron oxide nanoparticles from different bacteria, namely Magnetospirillum magneticum strain AMB-1 190,191 (Fe 3 O 4 , after removing the magnetosome membrane), Burkholderia sp. YN01v 192,193 (Fe 3 O 4 ), Comamonas testosterone 194 (Fe 1.44 O 0.32 (OH) 3.86 ), and Acinetobacter strains 195 (Fe 0.96 O 0.88 (OH) 1.12 ), exhibited intrinsic POD-like, 190–195 SOD-like, 193 and CAT-like activities. 193 These bacteria belong to the Gram-negative group and are widespread everywhere on the Earth, including marine habitats.…”
Section: Introductionmentioning
confidence: 99%
“…YN01v 192,193 (Fe 3 O 4 ), Comamonas testosterone 194 (Fe 1.44 O 0.32 (OH) 3.86 ), and Acinetobacter strains 195 (Fe 0.96 O 0.88 (OH) 1.12 ), exhibited intrinsic POD-like, 190–195 SOD-like, 193 and CAT-like activities. 193 These bacteria belong to the Gram-negative group and are widespread everywhere on the Earth, including marine habitats. 196–199 In addition, magnetotactic bacteria can be traced back to the Archean era, and thus constitute one of the oldest organisms known to exist on the planet today.…”
Section: Introductionmentioning
confidence: 99%